The woman who loved mankind : the life of a twentieth-century Crow elder Lillian Bullshows Hogan as told to Barbara Loeb & Mardell Hogan Plainfeather. - Hogan, Lillian Bullshows, 1904-2003 (University of Nebraska Press, 2012)
The oldest living Crow at the dawn of the twenty-first century, Lillian Bullshows Hogan (1905-2003) grew up on the Crow reservation in rural Montana. In The Woman Who Loved Mankind she enthralls readers with her own long and remarkable life and the stories of her parents, part of the last generation of Crow born to nomadic ways. As a child Hogan had a miniature teepee, a fast horse, and a medicine necklace of green beads; she learned traditional arts and food gathering from her mother and experienced the bitterness of Indian boarding school. She grew up to be a complex, hard-working Native woman who drove a car, maintained a bank account, and read the local English paper but spoke Crow as her first language, practiced beadwork, tanned hides, honored clan relatives in generous giveaways, and often visited the last of the old chiefs and berdaches with her family. She married in the traditional Crow way and was a proud member of the Tobacco and Sacred Pipe societies but was also a devoted Christian who helped establish the Church of God on her reservation. Warm, funny, heartbreaking, and filled with information on Crow life, Hogan's story was told to her daughter, Mardell Hogan Plainfeather, and to Barbara Loeb, a scholar and longtime friend of the family who recorded her words, staying true to Hogan's expressive speaking rhythms with its echoes of traditional Crow storytelling. -- Publisher.